Female accountants in partnership positions: Persona non grata? - Zopiatis, Anastasios; Krambia-Kapardis, Maria (My University, 2009)
Purpose – Although the proportion of women accountants is rising steadily, their number in partnership position remains constant. This article explores this phenomenon in an attempt (a) to identify the reasons behind it and (b) clarify which are the barriers that hinder female accountants from being in the top echelon of the accounting practice in an emerging economy like Cyprus. Methodology/approach – The study reported in this article builds on two previous studies, quantitative in nature, carried out by one of the present authors. Utilising the findings of the two earlier studies, the authors use a qualitative approach to further explore the reasons as to why there is a ‘concrete wall’ for women in accounting practices at partnership level. Findings – In contrast to other studies, the present study found that the prohibiting factor creating the barrier is not motherhood but the cultural attitudes and expectations of men imposed on mothers. Another finding is that despite the fact that there is a bigger pool of women today in senior manager positions, it is uncertain if the proportion of female partners will rise in a decade. Research limitations – Although the qualitative study utilising interviews of both genders identified interesting concerns for the local accounting profession, these findings cannot be representative of all emerging economies. Practical implications – The article adds to existing knowledge by clarifying the reasons discouraging women accountants from reaching partnership positions. Findings are of interest to industry stakeholders who wish (a) to attract more women accountants to partnership positions and (b) to develop an environment that addresses women's concerns and enhances their career aspirations towards reaching the top echelon of their profession. Originality/value of article – Most research in this field utilises quantitative or qualitative research independently. In this research we utilise the results of the quantitative studies to indentify in depth the ‘real’ rather than the ‘imaginary’ barrier facing women accountants from entering partnership. Furthermore, this is the first time this is studied in an emerging economy, whereas all other studies are in developed economies.
Keywords: Women accountants; Partnership; Women; Partnership level